RETRACTED: The Effect of MCM3AP-AS1/miR-211/KLF5/AGGF1 Axis Regulating Glioblastoma Angiogenesis - Yang, Chunqing; Zheng, Jian; Xue, Yixue; Yu, Hai; Liu, Xiaobai; Ma, Jun; Liu, Libo; Wang, Ping; Li, Zhen; Cai, Heng; Liu, Yunhui (Frontiers in Molecular Neuroscience, 2018)
Glioblastoma (GBM) is the most aggressive and malignant primary tumor. Angiogenesis plays a critical role in the progression of GBM. Previous studies have indicated that long non-coding RNAs (lncRNAs) are abnormally expressed in various cancers and participate in the regulation of the malignant behaviors of tumors. The present study demonstrated that lncRNA antisense 1 to Micro-chromosome maintenance protein 3-associated protein (MCM3AP-AS1) was upregulated whereas miR-211 was downregulated in glioma-associated endothelial cells (GECs). Knockdown of MCM3AP-AS1 suppressed the cell viability, migration and tube formation of GECs and played a role in inhibiting angiogenesis of GBM in vitro. Furthermore, knockdown of MCM3AP-AS1 increased the expression of miR-211. Luciferase reporter assay implicated that miR-211 targeted KLF5 3′-UTR and consequently inhibited KLF5 expression. Besides, in this study we found that MCM3AP-AS1 knockdown decreased KLF5 and AGGF1 expression by upregulating miR-211. In addition, KLF5 was associated with the promoter region of AGGF1. Knockdown of KLF5 decreased AGGF1 expression by transcriptional repression, and also inhibited the activation of PI3K/AKT and ERK1/2 signaling pathways. Overall, this study reveals that MCM3AP-AS1/ miR-211/ KLF5/ AGGF1 axis plays a prominent role in the regulation of GBM angiogenesis and also serves as new therapeutic target for the anti-angiogenic therapy of glioma.